Catalytic Transesterification of Used Cooking Oil to Biodiesel: Effect of Oil-Methanol Molar Ratio and Reaction Time - Diah Ayu; Rizca Aulyana; Esti Widya Astuti; Kusmiyati Kusmiyati; Nur Hidayati (Automotive Experiences, 2019)
Used cooking oil has the potential as biodiesel so that it can reduce environmental pollution. Transesterification of triglycerides in used cooking oil with an alcohol to form methyl esters of fatty acids or biodiesel and glycerol. The type of catalyst is one of the determinants of the transesterification reaction and coal fly ash has the potential to be used as a catalyst in the production of biodiesel. Therefore, this study aims to examine the effect of the oil-methanol ratio and the time of the transesterification of used cooking oil to the yield of biodiesel produced using an alkali-activated fly ash catalyst. Transesterification is carried out at 60 °C, the stirring speed is 700 rpm, and the amount of catalyst load is 4%. The result, the highest yield of biodiesel reached almost 89%. This biodiesel consists of 48.86% methyl oleate and 33.86% methyl palmitate and has a density that meets the Indonesian National Standard, which is 0.85 - 0.90 g/cm3. Finally, the BET test on the fly ash catalyst shows a catalyst surface area of ​​around 104.106 m2/g.